2009
DOI: 10.1002/elps.200900039
|View full text |Cite
|
Sign up to set email alerts
|

Current separation and detection methods in microdialysis the drive towards sensitivity and speed

Abstract: This review outlines some of the analytical challenges associated with the analysis of microdialysis (MD) samples, in particular, the minute complex sample volumes that are often encountered. In MD sampling many different low-molecular-weight molecules can be collected, but the research findings are often limited by the sensitivity, specificity, and reliability of the analytical technique that is coupled to the dialysis probe. Therefore it is critical that a lot of consideration is given in selecting the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…Microdialysis usually results in the collection of minute sample volumes; the order of a few microliters. In our study, UHPLC has demonstrated that it is capable of handling sample volumes of 1 l or less, which is ideal for coupling with microdialysate sampling, whereas the more conventional LC systems usually require greater than 5 l sample volumes [30]. …”
Section: Introductionmentioning
confidence: 92%
“…Microdialysis usually results in the collection of minute sample volumes; the order of a few microliters. In our study, UHPLC has demonstrated that it is capable of handling sample volumes of 1 l or less, which is ideal for coupling with microdialysate sampling, whereas the more conventional LC systems usually require greater than 5 l sample volumes [30]. …”
Section: Introductionmentioning
confidence: 92%
“…High performance liquid chromatography (HPLC)-based analytical methods are largely employed in microdialysis studies (Cheng et al, 2009; Guihen and O’Connor, 2009). With regard to EtOH and ACD determination HPLC-based methods appear particularly suitable, since samples are not heated during analysis and thus heat sensitive or volatile compounds (such as EtOH and ACD) can be efficiently separated.…”
Section: In Vivo Etoh and Acd Detection: Invasive Approachesmentioning
confidence: 99%
“…Pharmacokinetic parameters were determined in both the plasma and the tumor following treatment with a STEALTH liposomal formulation of a camptothecin analog [104] . Online Analysis Using Liquid Chromatography The direct coupling of liquid chromatography to the microdialysis sampling system has several advantages, and this has recently been reviewed by several groups [15,19,56,105,106] . The use of online injectors allows the manipulation of submicroliter sample volumes, thereby improving temporal resolution in comparison to off -line systems.…”
Section: Off -Line Analysis Using Liquid Chromatographymentioning
confidence: 99%